Analysis of the Cochrane Review: Interventions for Improving Upper Limb Function after Stroke. Cochrane Database Syst Rev. 2014,11:CD010820. - Sousa Nanji, Liliana (2015)
Impairment of the upper limbs is quite frequent after stroke, making rehabilitation an essential step towards clinical recovery and patient empowerment. This review aimed to synthetize existing evidence regarding interventions for upper limb function improvement after Stroke and to assess which would bring some benefit. The Cochrane Database of Systematic Reviews, the Database of Reviews of Effects and PROSPERO databases were searched until June 2013 and 40 reviews have been included, covering 503 studies, 18 078 participants and 18 interventions, as well asdifferent doses and settings of interventions. The main results were: 1- Information currently available is insufficient to assess effectiveness of each intervention and to enable comparison of interventions; 2- Transcranial direct current stimulation brings no benefit for outcomes of activities of daily living; 3- Moderate-quality evidence showed a beneficial effect of constraint-induced movement therapy, mental practice, mirror therapy, interventions for sensory impairment, virtual realityand repetitive task practice; 4- Unilateral arm training may be more effective than bilateral arm training; 5- Moderate-quality evidence showed a beneficial effect of robotics on measures of impairment and ADLs; 6- There is no evidence of benefit or harm for technics such as repetitive transcranial magnetic stimulation, music therapy, pharmacological interventions, electrical stimulation and other therapies. Currently available evidence is insufficient and of low quality, not supporting clear clinical decisions. High-quality studies are still needed.